2019
DOI: 10.1055/s-0039-1691767
|View full text |Cite
|
Sign up to set email alerts
|

Two-Hourly versus Three-Hourly Feeding in Very Low-Birth-Weight Infants: A Systematic Review and Meta-Analysis

Abstract: Objective This study aimed to systematically review and meta-analyze the benefits and side effects of 3-hourly versus 2-hourly feeding intervals in very low-birth-weight (VLBW) infants. Study Design Database search include PubMed and Cochrane CENTRAL databases from inception until March 3, 2019. The author extracted the data from included studies and used Cochrane-GRADE approach to assess the quality of the evidence. Results Seven studies—four randomized controlled trials (RCTs) and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Bolus feeds promote cyclical release of gastrointestinal tract hormones to stimulate gut maturation and motility (208) but marked variations in practice exist and many use continuous feeds (183). Low‐quality evidence suggests feeding 3‐hourly is comparable to 2‐hourly feeding although extremely low‐birth‐weight infants may reach full enteral feeds earlier when fed 2‐hourly compared with 3‐hourly (209). Bolus feeding increases splanchnic perfusion more than continuous feeding (210).…”
Section: Feeding Mode: Gastric Tube and Bolus Or Continuous Feeding (...mentioning
confidence: 99%
“…Bolus feeds promote cyclical release of gastrointestinal tract hormones to stimulate gut maturation and motility (208) but marked variations in practice exist and many use continuous feeds (183). Low‐quality evidence suggests feeding 3‐hourly is comparable to 2‐hourly feeding although extremely low‐birth‐weight infants may reach full enteral feeds earlier when fed 2‐hourly compared with 3‐hourly (209). Bolus feeding increases splanchnic perfusion more than continuous feeding (210).…”
Section: Feeding Mode: Gastric Tube and Bolus Or Continuous Feeding (...mentioning
confidence: 99%
“…The content of the questionnaire includes neonatal and maternal socio-demographic variables (gestational age, birth weight, age of the mother, residence and educational status), neonatal (first and fifth minutes APGAR score, meconium passage, sucking reflex, continuous positive air pressure, perinatal asphyxia, hemodynamic instabilities, birth defect, obstructions, respiratory distress syndrome, meconium aspiration syndrome, blood transfusion, phototherapy) and maternal related factors (sero-status of the mother, hypertensive disorder during pregnancy, mode of delivery, birth type, place of delivery, parity, postpartum hemorrhage and diabetes mellitus) and health service-related factors (frequency of order revision). The data extraction checklist and questionnaire were adapted from different related literature, books, and guidelines [17,26,[31][32][33][34][35][36][37][38][39].…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…In VLBW infants, systematic reviews and meta-analyses concluded that while using intermittent feeding, 3-hourly versus 2-hourly feeding intervals are comparable, although extremely low-birth-weight (ELBW) infants (birth weight < 1000 g) may reach full enteral feeds earlier when fed twice-hourly 44,45 .…”
Section: Bolus Versus Continuous Feedingmentioning
confidence: 99%
“…In brief, in VLBW infants, continuous and intermittent bolus feeding seem comparable, as are comparable 3-hourly or 2-hourly feeding intervals in intermittent feeding (LOE 3) 4,20 . In infants < 1000 g, a 2-hourly interval may be preferable (LOE 3) 44,45 .…”
Section: Bolus Versus Continuous Feedingmentioning
confidence: 99%